Architecture model proposal of innovative intelligent manufacturing in the chemical industry based on multi-scale integration and key technologies. (4th October 2020) - He, Ge; Dang, Yagu; Zhou, Li; Dai, Yiyang; Que, Yi; Ji, Xu
Highlights: Elaborates interconnected chemical engineering architecture and key technologies. Integrates intelligent technologies like IoT, cloud computing in chemical industry. Chemical multi-scale integrated intelligent manufacturing model is proposed. Abstract: The manufacturing of chemical products is realized through the controlled conversion and transfer of mass and energy by chemical processes that have the characteristics of heterogeneity, nonlinearity, non- equilibrium, multiple scale, and multiple temporal–spatial domains. The key to the development of intelligent manufacturing in the chemical industry is to achieve interconnected synergy and process efficiency under multi-scale conditions. On the one hand, the understanding and regulation of the multi-scale interconnection mechanism of chemical processes is important for the safe and reliable operation of chemical process systems. On the other hand, achieving the multi-scale interconnection, integration, and synergy of chemical processes allows green development of the chemical industry. However, through extensive research into the multi-scale chemical industry mechanisms, an integrated conceptual framework models for intelligent manufacturing have yet not been developed. On this basis, we propose a multi-scale and integrated intelligent manufacturing model for the chemical industry; that is, interconnected chemical engineering. This paper elaborates the concept, goals, characteristics, and architecture of interconnected chemical engineering and discusses key technologies relating to interconnected chemical engineering, including multi-level cyber-physical systems in the chemical industry, cloud manufacturing, full life-cycle security management technologies, dynamic security monitoring and decision-making models under a coupled interlocking mechanism, and blockchain-based interconnected chemical data security technologies. Graphical abstract: Image, graphical abstract